Ridicule, deconstruction, reflection, and identity: Christian elements and thematic expression in Feng Xiaogang’s films - Qiang Zhou; Muhammad Yaqoub (Humanities & Social Sciences Communications)
Abstract Due to cultural policies, film censorship, and the history of foreign imperialism in China, Christianity is perceived to carry a Western ideology and is rarely depicted in mainstream Chinese films and dramas. Director Feng Xiaogang is a unique example of a filmmaker who has incorporated Christian elements into several of his films. This study examines how Christian elements manifest in Feng’s films by analyzing the evolution of Feng’s approach towards Christianity from ridicule with deconstruction to reflection and identification with the tenets of the faith. Feng skillfully circumvents prevailing cultural, social, and political constraints to incorporate thematic elements such as redemption, life, and death into his films, providing audiences with strong emotional experiences and value recognition. These dynamics take place within the interrelated contexts of Feng’s status as a military veteran, Chinese cultural policies and film censorship mechanisms, and the rapid growth of Christianity in post-Mao China. This article is useful for filmmakers exploring religious symbolism in constrained environments, scholars of Chinese cinema and cultural policy, and policymakers examining the intersection of ideology, censorship, and artistic expression.